Vitamin D Supplementation Improves Muscle Mass, Physical Function, and Quality of Life in Patients With Degenerative Lumbar Disease - Sinsuda Dechsupa; Wicharn Yingsakmongkol; Worawat Limthongkul; Weerasak Singhatanadgige; Suvichada Assawakosri; Sittisak Honsawek (Clinical and Translational Science)
ABSTRACT Degenerative lumbar disease is a significant contributor to acute or chronic musculoskeletal issues in the elderly, often associated with low serum 25‐hydroxyvitamin D (25(OH)D) levels. The effect of vitamin D2 supplementation on muscle mass, strength, and physical performance remains unclear. This study aimed to determine the effect of vitamin D2 supplementation on these parameters in patients with degenerative lumbar disease and low vitamin D status. A total of 115 patients with serum 25(OH)D levels < 30 ng/mL were administered 40,000 IU of vitamin D2 (ergocalciferol) weekly for 6 months. Body composition, serum 25(OH)D, parathyroid hormone (PTH) levels, muscle strength, and physical performance were examined before and after 6 months of vitamin D2 supplementation. Baseline median serum 25(OH)D was 24.9 ng/mL; 79.1% had vitamin D insufficiency, and 20.9% had vitamin D deficiency. After supplementation, median 25(OH)D increased to 43.1 ng/mL (p < 0.001), with a significant reduction in PTH (p < 0.001). Significant improvements were observed in muscle mass (p = 0.04), balance test (p = 0.01), gait speed (p = 0.009), chair stand test (p < 0.001), short physical performance (p < 0.001), Oswestry disability index (p < 0.001), and visual analog scale (VAS) scores (p < 0.001). Post‐supplementation 25(OH)D levels correlated negatively with body mass index (ρ = −0.187, p = 0.045), fat mass (ρ = −0.219, p = 0.019), fat percentage (ρ = −0.199, p = 0.033), and VAS score (ρ = −0.313, p < 0.001). Six months of vitamin D2 supplementation significantly improved vitamin D status, muscle mass, physical performance, and quality of life in patients with degenerative lumbar disease.